The Feasibility and Practicality of a Simple Fountain Teaching Aid in Boyle's Law Material - Kurduka, Dewi Yana; Reski, Andi; Palittin, Ivylentine Datu; Nhu Le, Nguyen (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2024)
This study aims to test the feasibility and practicality of the developed product. The product developed is a simple fountain teaching aid related to the concept of Boyle's Law material. The product developed in the study uses a 4D model consisting of four stages, namely define, design, develop, and disseminate. The instruments used in collecting data are in the form of a feasibility questionnaire and a practicality questionnaire. The feasibility of the product is assessed by 3 experts while the practicality of the product is assessed by 3 validators. And based on the response test of 36 high school students in grade X to describe student responses to the product. The results of the validator's assessment show that the product developed is very feasible while the results of the student response test show that the product developed is very practical. So it can be concluded that the product developed in this study in the form of a simple fountain teaching aid is feasible and practical to use in the physics learning process of high school in grade X.